2020
DOI: 10.1007/s00192-020-04273-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-time assessment of the behaviour of the bladder neck and proximal urethra during urine leaking in the cough stress test (CST) in supine and standing positions using transperineal ultrasound

Abstract: Introduction and hypothesis The objective was to describe the behaviour of the bladder neck and proximal urethra during urine leaking in the cough stress test (CST) in supine and standing positions using transperineal ultrasound (TPUS). Method We carried out prospective data collection and a retrospective data analysis of 102 women with stress urinary incontinence (SUI) who had a positive CST with TPUS in the supine and/or standing position. On TPUS, the behaviour of the bladder neck and proximal urethra was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 22 publications
(38 reference statements)
1
21
2
3
Order By: Relevance
“…As bladder pressure is higher in standing than sitting or supine, 12 and standing reduce support from the perineum, maintenance of continence is likely to be more challenging in this body position. This has been reported for women, 13 and suggested, although not shown, in men. 11 Recent work using TPUS has shown that position and displacement (with contraction) of pelvic landmarks associated with PFM contraction differs between sitting and standing.…”
Section: Introductionsupporting
confidence: 56%
“…As bladder pressure is higher in standing than sitting or supine, 12 and standing reduce support from the perineum, maintenance of continence is likely to be more challenging in this body position. This has been reported for women, 13 and suggested, although not shown, in men. 11 Recent work using TPUS has shown that position and displacement (with contraction) of pelvic landmarks associated with PFM contraction differs between sitting and standing.…”
Section: Introductionsupporting
confidence: 56%
“…Although in the standing position the structures of the anterior compartment lie lower than in the lithotomy position, the differences are small and not of clinical signi icance [8]. The relative bladder neck mobility itself is shown not to be affected by the examination position [9,10].…”
Section: Patient Population and Proceduresmentioning
confidence: 86%
“…Previous studies showed transperineal ultrasound could record real-time urine leakage and describe the anatomic changes in SUI. There were differences regarding bladder neck configuration and mobility during urinary leakage in supine and standing positions [3]. However, the mid-urethral mobility rather than the bladder neck mobility may account for SUI [11].…”
Section: Zusammenfassungmentioning
confidence: 92%